Comparative evaluation of GPR versus APRI and FIB‐4 in predicting different levels of liver fibrosis of chronic hepatitis B. Issue 5 (4th January 2018) - Liu, D.‐P.; Lu, W.; Zhang, Z.‐Q.; Wang, Y.‐B.; Ding, R.‐R.; Zhou, X.‐L.; Huang, D.; Li, X.‐F.
Summary: It is of great significance to develop and evaluate noninvasive indexes predicting the level of liver fibrosis. The aim of this study was to comparatively evaluate gamma‐glutamyl transpeptidase‐to‐platelet ratio (GPR) versus aspartate aminotransferase‐to‐platelet ratio index (APRI) and fibrosis index based on 4 factors (FIB‐4) in predicting different levels of liver fibrosis of chronic hepatitis B (CHB) within the framework of HBeAg‐positive and HBeAg‐negative patients. A total of 1157 HBeAg‐positive and 859 HBeAg‐negative CHB patients were enrolled, among whom the pathological stage ≥S2, ≥S3, ≥S4 were defined as significant fibrosis, extensive fibrosis and cirrhosis, respectively. Receiver operating characteristic (ROC) curves were used to evaluate the performance of GPR, APRI and FIB‐4 in predicting different levels of liver fibrosis. In HBeAg‐positive patients, the area under ROC curves (AUROCs) of GPR in predicting extensive fibrosis and cirrhosis were both significantly larger than those of APRI ( P  =   .0001 and P  <   .0001). In HBeAg‐negative patients, the AUROCs of GPR in predicting significant fibrosis and cirrhosis were significantly larger than those of FIB‐4 ( P  =   .0006 and P  =   .0041). The AUROC of GPR in predicting extensive fibrosis was significantly larger than that of APRI and FIB‐4 ( P  =   .0320 and P  =   .0018). Using a cut‐off of GPR > 0.500 as standard, the sensitivities and specificities of GPR in predicting significant fibrosis in HBeAg‐positive patients were 59.6% and 81.2%, and for cirrhosis 80.9% and 63.8%, respectively; and those of HBeAg‐negative patients were 60.3% and 78.3%, 84.5% and 66.1%, respectively. Regardless of HBeAg‐positive or HBeAg‐negative status, GPR had the best performance in predicting different levels of liver fibrosis.